Modelagem hidrológica e hidráulica a partir de dados TRMM aplicada a análise de risco em áreas inundáveis: estudo de caso no município de Atalaia - Brito, Tainara Ramos da Rocha Lins de (2017)
This work consisted in the analysis of the off-line coupling of hydrological and hydraulic models from observed rainfall data and in the TRMM satellite precipitation intensity estimates in the Paraíba do Meio watershed (AL/PE), with the final objective the mapping of flooded areas and risk analysis of Atalaia-AL city, when considering the flood event occurred in 2010. The main computational programs used were: HEC-HMS in hydrological modeling and HEC-RAS in hydraulic modeling, in addition to their respective extensions integrated with ArcMap in the preprocessing stage, HEC-GeoHMS and HEC-GeoRAS. The results showed that the rainfall intensity data estimated by the TRMM satellite presented a good correlation with the rainfall data series, presenting values of 0.90 ("TRMM" x Postos) and 0.94 ("TRMM + Postos" x Postos). The hydrological model presented a good representation in relation to flood events in the Paraíba do Meio watershed, from data the flood occurred in 2000 and the flood of 2010. The validation of the model presented satisfactory results in the Atalaia post (39870000) in relation to the corrected satellite series ("TRMM + Postos"), evidencing with a Nash Sutcliffe coefficient - COE of 0.91. The hydraulic modeling was calibrated based on the Manning coefficient (n) adjustment for the banks and bottom of the channel, based on the ENGEMAP field markings and the peak flow recorded during the 2010 event by the fluviometric Atalaia post (39870000), already the model validation was done from the calibrated Manning coefficient (n) and the hydrograph generated in the hydrological simulation based on the corrected satellite series TRMM ("TRMM + Postos"). Thus, the mapping of the flooded areas made based on the 2010 flood data allowed a Risk Analysis in Atalaia city, based on the threat and vulnerability of the resident population in the riverine region to the occurrence of floods.